Experimental evaluation of traction characteristics of the multi-support irrigation machine "Kuban-LK1" - Ryazantsev Anatoly; Evseev Evgeny; Antipov Alexey; Malko Igor (EPJ Web of Conferences)
The article proves that the optimization of the running gear parameters for the multi-support irrigation machine "Kuban-LK1" is based on optimizing the "rain - irrigation surface - irrigation machine" system, which determines the energy-traction properties of the machine. The paper examines the influence of soil adhesion and the height of soil grousers (depending on wear) of the pneumatic tires on the machine's trolleys on the aforementioned characteristics. Laboratory research data is presented, indicating the practical absence of soil sticking to the tires due to its washoff by the force impact of artificial rain. It is pointed out that the irrigation machine provides the necessary energy-traction properties across the entire range of irrigation rates. A slight decrease in these properties is observed at increased water supply rates (400 m³/ha and above), while an increase is noted when changing the direction and height of the soil grousers.